2002
DOI: 10.1073/pnas.162653499
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity, population regulation, and the stability of coral-reef fish communities

Abstract: Unprecedented population declines and extinctions because of human activities, combined with a growing recognition that such losses affect the stability of ecosystems, underscore the need to better understand how populations persist naturally. We provide field experimental evidence that high biodiversity-in particular, the combined effects of predators and competitors-acts in a way that regulates the size of local fish populations within their coral-reef community. These results indicate that complex interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 32 publications
6
104
0
Order By: Relevance
“…A major goal of MPAs should be the protection of species having disproportionate ecological importance, such as apex predators that function as keystones in structuring coral reef ecosystems (Carr et al 2002). The conservation of keystones should have high management priority.…”
Section: Implications For Marine Protected Area Designmentioning
confidence: 99%
“…A major goal of MPAs should be the protection of species having disproportionate ecological importance, such as apex predators that function as keystones in structuring coral reef ecosystems (Carr et al 2002). The conservation of keystones should have high management priority.…”
Section: Implications For Marine Protected Area Designmentioning
confidence: 99%
“…(1) longshore current flow from the southeast may deliver larval fish to South Bock about 1 wk later than to SE LSI, and (2) tidally driven current velocities at South Bock, which are 3 times higher than at SE LSI (Anderson et al 2002), may inhibit settlement of fish near the new moon when current velocities should be highest.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple observational studies have been conducted on continuous reefs that did detect density-dependent mortality: the honeycomb grouper Epinephelus merra at Réunion Island (Letourneur et al 1998) and both the bicolor damselfish Stegastes partitus and the bluehead wrasse at Barbados (Hunte von Herbing & Hunte 1991, Tupper & Hunte 1994. Considering experimental approaches, Carr et al (2002) demonstrated that mortality of the bicolor damselfish was density-dependent on both patch reefs and continuous reefs in the Bahamas. Also, on continuous reefs in the Bahamas, Webster (2003) demonstrated density dependence in the fairy basslet Gramma loreto.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also likely that direct and indirect behavioral interactions could exclude taxa from co-occurring within the same patch of habitat. Carr et al (2002) showed that negative interactions of both predators and competitors regulate local patterns of community composition. Positive interactions, on the other hand, such as those Sphyraena barracuda Great Barracuda F Trophic levels are defined as: H, herbivore; P, planktivore; B, browser; Mi, microinvertivore; Ma, macroinvertivore; F, piscivore.…”
Section: Discussionmentioning
confidence: 99%